Obszary aksjologiczne we współczesnych organizacjach - Wojewódzki, Tadeusz (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
Many problems of contemporary organizations originate in the area of axiology. In management practice, however, the problem of values is often reduced to stimulus-motivation of behavior and does not exceed the paradigm of socio-technical effectiveness. This is why strictly axiological problems are not identified and recognized as axiological but are often referred to in terms of their technical or economic consequences. In result, management practice deals rather with effects than actual causes of experienced problems. From the point of view of methodology of decision-making such state-of-affairs requires intervention. There are at least two ways to recommend changes with respect to such situation. First one, direct way, involves promoting axiological reflection among managers. Second one, the indirect, seeks to stimulate axiological consciousness through management consulting products that are built on essential axiological theory. The following paper focuses on the second of above mentioned ways and discusses particular consulting product called MSE™. On the one hand, the cognitive benefits of application of the MSE™ consist in implementation and validation of theory of integrated humanities in organizational context. Practical benefits, on the other hand, rely on opportunities emerging from MSE™ that allow for diagnosis of intellectual mental infrastructure of contemporary organizations and changes recommendation resulting therefrom.